Marriage and parenthood (London : Friends' Book Centre)
1934-11 1934 1930s 22 pages The Engagement 7 effort amply justified. The lot of the middle-aged woman who has had no interests outside her home and family, and finds herself suddenly bereft of these when her children leave home, is one of life's tragedies. To Friends, marriage is not simply a civil contract but a religious act. In the simple Quaker wedding, with the equal promise made by man and woman without the intervention of priest or minister, husband and wife come quietly into the presence of God to consecrate to His service the new life on which they are entering. With high hope and trust they face the future, remembering that "happiness and blessing in marriage depend first on the presence of devoted love, a love which is not the outcome of a mere passing attraction, but which includes a real respect by each for the personality of the other...... It will yield its fairest fruit as it is chastened by the discipline of care and trial bravely borne, and ripened into self-forgetting devotion by the mutual influence of parents and children." (Friends' Christian Practice, p.50.) 15X/2/478/6